On Information Explosion - Sarada Balasubramanian, Alladi (DESIDOC Journal of Library & Information Technology, 2002)
The rat-race among scientists has led to indiscriminate publishing of scientific literature resulting in the almost uncontrollable explosion of scientific information. Now the slogan is no longer Publish or Perish, but Publish and Perish. Currently leading scientists all over the world are preoccupied with this problem and are devising ways and means of arresting this flood of publications. Among the many suggestions made a few are examined in detail, chief among which is the vital role played by the editors of archival journals in sifting the more important from the less significant publications. The axe must fall at the very base of publication. Journal authors 'and editors must find a solution between themselves, in the larger interest of the scientific communication. http://dx.doi.org/10.14429/dbit.11.5.3039